Halal Digital Marketing Strategy to Increase Global Access for Sharia Micro, Small, and Medium Enterprises - Hakim, Lukman; Iswanto, Bambang; Hafeez, Humairah (IAIN Manado, 2025)
The growth of the digital economy presents significant opportunities for Sharia Micro, Small, and Medium Enterprises (MSMEs) to reach global markets through halal-compliant digital marketing strategies. However, challenges such as limited digital literacy, low halal certification rates, and the weak integration of Islamic ethical values with modern marketing practices remain critical barriers. This study aims to identify and synthesize effective halal digital marketing strategies that enhance global access for Sharia MSMEs while highlighting the role of local wisdom as a contextual strength. Using the Systematic Literature Review (SLR) method, this research analyzed 30 indexed articles from reputable databases (ScienceDirect, Emerald, Taylor & Francis, ResearchGate, and SINTA) published between 2015–2025. The findings reveal that effective halal digital marketing strategies combine the integration of fiqh muamalah principles, halal branding and certification legitimacy, and digital empowerment through ethical use of e-commerce and social media. Moreover, local wisdom, such as community-based entrepreneurship, religious trust networks, and cultural authenticity, serves as a moderating factor that strengthens the sustainability and social acceptance of halal marketing initiatives. Mechanisms to overcome key challenges include targeted digital literacy training, government-backed halal certification support, and collaborative partnerships among MSMEs, academia, and Islamic financial institutions. This study contributes to the existing body of knowledge by offering an integrated model that bridges global halal marketing frameworks with localized cultural and ethical practices, providing a replicable reference for other regions. Future research should test the proposed model through mixed-method or experimental approaches to measure its effectiveness across diverse socio-economic and regional contexts.